Efficient motion sensing algorithm for camera-enabled mobile devices - Chang, Yoong Choon; Neo, Tse Kian; Lim, Kok Chen (IEEE, 2007)
In this paper we present an efficient motion sensing algorithm for camera-enabled mobile device. In our algorithm, we first perform colour space acquisition to extract red colour component from ARBG colour space before applying motion estimation. Full-search Block Matching Algorithm (FBMA) is used for motion estimation due to its simplicity for mobile environment. After getting the estimated motion vector, we then perform a future motion prediction in order to produce-a better and smoother motion output. Finally, we implemented and tested our algorithm on the Nokia N73 phone using Java J2ME programming language.